Production of Kojic acid from sago hampas using combination of different aspergillus strains via solid state fermentation - Siti Nuraishah, Binti Salehhudin (Universiti Malaysia Sarawak, UNIMAS, 2013)
Kojic acid (5-hydroxy-2-hydroxymethyl-4-pyrone) is a depigmenting agent produced by several species of fungi, particularly Aspergillus flavus. In this work, the production of kojic acid using combination of different Aspergillus strains was investigated. Three sets of fermentation were carried out using individual culture of A. flavus Link 44-1, A. flavus NSH9 and combination of both strains in a culture. Single-strain A.flavus Link 44-1 at inoculum size of 107 spores/ml exhibit the highest production of kojic acid which is 9.5 g/L. This result indicates the feasibility of single-strain A. flavus Link 44-1 as potential strain for the production of kojic acid using sago hampas as substrate. The effects of different spore concentration ranging from 105 spores/ ml to 108 spores/ ml on kojic acid production was tested. Throughout this work, the potential of utilizing multi-strains as an alternative to single-strain inoculum for kojic acid fermentation was examined.